CD90+ liver cancer cells modulate endothelial cell phenotype through the release of exosomes containing H19 lncRNA - Conigliaro, Alice; Costa, Viviana; Lo Dico, Alessia; Saieva, Laura; Buccheri, Simona; Dieli, Francesco; Manno, Mauro; Raccosta, Samuele; Mancone, Carmine; Tripodi, Marco; De Leo, Giacomo; Alessandro, Riccardo (Molecular cancer, 2015)
Background CD90+ liver cancer cells have been described as cancer stem-cell-like (CSC), displaying aggressive and metastatic phenotype. Using two different in vitro models, already described as CD90+ liver cancer stem cells, our aim was to study their interaction with endothelial cells mediated by the release of exosomes. Methods Exosomes were isolated and characterized from both liver CD90+ cells and hepatoma cell lines. Endothelial cells were treated with exosomes, as well as transfected with a plasmid containing the full length sequence of the long non-coding RNA (lncRNA) H19. Molecular and functional analyses were done to characterize the endothelial phenotype after treatments. Results Exosomes released by CD90+ cancer cells, but not by parental hepatoma cells, modulated endothelial cells, promoting angiogenic phenotype and cell-to-cell adhesion. LncRNA profiling revealed that CD90+ cells were enriched in lncRNA H19, and released this through exosomes. Experiments of gain and loss of function of H19 showed that this LncRNA plays an important role in the exosome-mediated phenotype of endothelial cells. Conclusions Our data indicate a new exosome-mediated mechanism by which CSC-like CD90+ cells could influence their tumor microenvironment by promoting angiogenesis. Moreover, we suggest the lncRNA H19 as a putative therapeutic target in hepatocellular carcinoma.